Analisis Rasio Profitabilitas pada PT Indofood Tbk Periode 2015-2024 - Nurwahyudi, Imam; Wulandari; Juwani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the profitability ratios of PT Indofood Tbk during the 2015–2024 period by examining Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The research employed a descriptive quantitative approach using secondary data obtained from the company's financial statements. Data analysis was conducted through simple linear regression, correlation analysis, coefficient of determination, and partial hypothesis testing (t-test) using SPSS version 23. The findings indicate that ROA, ROE, and NPM have positive relationships with net profit; however, their effects are not statistically significant. The significance values obtained were 0.281 for ROA, 0.575 for ROE, and 0.091 for NPM, all exceeding the 0.05 significance level. Furthermore, the coefficient of determination analysis shows that the profitability variables contribute substantially to explaining variations in net profit, although other factors outside the model also influence company performance. The results suggest that PT Indofood Tbk has not yet optimized the utilization of its assets, equity, and sales activities in generating maximum profitability. Therefore, improving operational efficiency and financial management is essential to enhance future financial performance.